Design and fabricate measuring starting block - Mohd Zaeed, Mohd Zin (2008)
Design and fabrication for measuring starting block for sprinter use many stell such as palte bar,u bar and etc.process to fabricate this product start from litereture review from market for easy to design this product. Concept important because smooth planning to fabricate this product.advantages and disadvantages from literature review use to make concept for this project.many process invold to make this product such as drilling, cutting and etc. measuring starting block import to sprinter and coach analysis their starting point.